Transient renal blood obliteration as an alternative to the study of renal ischemia-reperfusion syndrome in an animal model (Research, Society and Development, 2022)
The work aims at evaluating the viability of the transient renal blood obliteration method as an alternative to the study of renal CRS in Tayassu tajacu, considering the probable morphological and physiological similarity of this species to humans, since it presents phylogenetic proximity with domestic swine. Eight animals were used, which were submitted to a surgical procedure to induce ischemic nephropathy by clamping the renal vessels with vascular clamp for 60 minutes. Samples were collected for serum urea, creatinine and urinary protein / creatinine ratio (UPC), in addition to renal ultrasonographic evaluation, both before induction and on the 10th and 20th postoperative days, and collection of material for histopathological examination. The results showed a difference in the renal resistivity levels between the evaluated moments, an increase of renal echogenicity with loss of the cortico-spinal relation and presence of discrete glomerular alterations and several tubulointerstitial alterations in the histopathological analysis. It was concluded that the catheter is a good experimental model for studies of induced ischemic nephropathies, but it is necessary to standardize its renal, serological and urinary biochemical parameters in the same nutritional regimen, given the great variability of such data within the species.